Analysis of Different Diagnostis Methods of Influenza in Horses - Erdeljan, Mihajlo; Davidov, Ivana; Cutuk, Ramiz; Rogan, Dragan; Potkonjak, Aleksandar (Acta Scientiae Veterinariae, 2016)
Background: Equine Influenza is a serious, acute respiratory illness with characteristical clinical signs. The disease is caused by family of Orthomyxoviridae, genera Influenza virus A by two subtypes H7N7 and H3N8. Currently, there is believe that H7N7 has been replaced as a predominant subtype with the H3N8. Horse infection with influenza virus can be detected by serological tests on paired sera using HI test. Commercial rapid tests could be used for the detection of influenza virus. Recently it is widely use a PCR method as fast and more specific methods. Materials, Methods & Results: Fifty horses and one pony, age between one and 22 years have been included in experiment. Horses were of different race, sex, and age and vaccination status. Ten out of total 51 (10/51) have been regularly vaccinated against EI. Prior to initiation of these study epidemiological survey has been performed. The clinical examination has been followed by blood sampling for blood cell and serum extraction. The serums were evaluated by HI method. Nasal swabs are taken from both nostrils twice, one was frozen for virus detection by RT-qPCR while another was used for detection of EI virus by Directi-gen™ FLU A rapid test. Analysis of titers of antibody reveled that 7 horses (14%) had specific antibodies (IgG) against subtype H7N7, while 9 horses (18%) had specific antibodies against H3N8. In the same time 4 horses had specific antibodies against both subtypes. Serological data confirmed that from 48 horses (96%) had the titer of antibodies greater than 16 against H7N7, while 40 horses (80%) had the specific antibodies (IgG) against H3N8. We found quite unexpected presence of specific antibodies (IgG) for H7N7 in horses that have not been previously vaccinated with H7N7 subtype. These horses never been utilized for sport activity and there was no legal requirements for their vaccination. Could horses with specific antibodies for H7N7 be transfected from vaccinated horses we could not confirme with scientific evidence either we could not have evidence that wild and domestic birds played a significant role especially knowing that horses are dead end of further we could confirm it. Our findings unequivocally confirmed that EI virus subtype H7N7 antibodies (IgG) were present in horses that have not been vaccinated and this is serological evidence that virus H7N7 is circulating in these geographical areas. Discussion: Fast and reliable diagnosis and isolation of suspicious horses represent the first line of defense against pandemic influenza. Recognition of clinical signs (fever, depression, sharp cough and nasal discharge) along with epizootical survey provides the basis for the early detection of infection. In some cases, cough and rapid spread of symptoms of cough in a group of horses that were either unvaccinated against influenza virus or have been in contact with influenza virus infected horses can clearly point out to the EI virus. The definitive confirmation of EI virus could be done by virus isolation on tissue culture or embrionated eggs followed by detection of virus nucleic acid by RT-PCR. Our data suggest that a substantial number of horses (90%) that have not been vaccinated or vaccinated irregularly had specific antibodies against both subtypes of EI, what suggest that those horses have been exposed to viruses sometimes during their lifetime. Additionally, despite the fact that 20% of horses had some signs of respiratory disease that resemble EI we were not able to confirm EI nucleic acid by RT-PCR while Directi-gene™ assay confirmed virus presence just in two horses. Failure to detect virus nucleic acid could be due to fact that nasal swab samples have been taken at the end of the clinical symptoms, other authors have simular PCR negative patient which displayed a significant rising titre to influenza type A.